Концептуально-методичні засади оцінювання інноваційного розвитку соціально-економічних систем - Падерін, І.Д.; Горященко, Ю.Г. (Вісник економічної науки України, 2022)
Інформаційно-методичне забезпечення оцінювання інноваційного розвитку держави, регіонів та підприємств потребує удосконалення та новітніх теоретико-методологічних напрацювань. Основним завданням даного дослідження є розробка методу обрахунку інтегрального показника рівня інноваційного розвитку на щаблі екзогенної системи управління інноваційним процесом з метою виявлення стану і тенденцій інноваційного розвитку України. Проведено факторний аналіз показників, що характеризують інноваційний розвиток держави за період 2010-2019 рр., за допомогою методу модифікованої головної компоненти побудовано узагальнюючий показник. Уперше запропоновано інтегрований показник – рівень інноваційного розвитку соціально-економічних систем (держави, регіонів). Розроблено метод обчислення інтегрального показника рівня інноваційного розвитку України, що включає інституційно-соціальну, економічну, наукову, інформаційно-освітню та фінансову складові інноваційного розвитку. The purpose of this study is to develop a method for calculating an integrated indicator of the level of innovation development at the stage of exogenous innovation management system in order to identify the state and trends of innovation development in Ukraine. Methodology. The main research methods were analysis and synthesis, methods of statistical observation and generalization in the collection, grouping and analysis of statistics for 10 years. Another method was a comparative analysis in assessing the level of innovative development of Ukraine, in particular, all its components. The method was also used concrete and abstract comparative characteristics – in presenting the results, providing conclusions and research proposals. Results. The factor analysis of the indicators characterizing innovative development of the state for the period of 2010-2019 is carried out, by means of a method of the modified main component the generalizing indicator is constructed. The calculation of the generalized indicators of level of innovative development (LID) in 2010-2019 was carried out using the software SPSS 21. Practical implications. These practical recommendations can be applied not only in the Ukrainian business space, but also in the business of countries that have chosen innovative development. Value / originality. For the first time, an integrated indicator was proposed – the level of innovative development of socio-economic systems (states, regions). Conclusions. A method for calculating an integrated indicator of the level of innovative development of Ukraine, which includes institutional, social, economic, scientific, informational, educational and financial components of innovative development, has been developed.